Ostensiewe adressering in vertalende woordeboeke - Gouws, R.H. (Lexikos, 1994)
Ostensive Addressing in Translation Dictionaries From a semantic perspective the inclusion of translation equivalents can be regarded as the most important component of the lexicographical treatment in translation dictionaries. One seldom finds a complete agreement in the semantic scope of lemma and translation equivalent. Consequently the lexicographer has to include additional entries to achieve a relation of communicative equivalence between source and target language. The need for this additional information is especially noticeable in articles with an equivalent relation of semantic divergence. The polysemous character of the lemma compels the inclusion of different translation equivalents for each polysemous sense of the lemma. To assist the dictionary user in his choice of equivalents it is imperative that the equivalents should be complemented by contextual information. Pictorial illustrations can be employed as a microstructural type to enhance semantic disambiguation. This ostensive addressing is not used properly in Afrikaans translation dictionaries. In contrast to the widely accepted point of view that pictorial illustrations only have an encyclopedic function this paper emphasizes their semantic importance, the extent of their lexicographical function and their range of application. Although the primary utilization of ostensive addressing is found in the differentiation of senses in equivalent relations of semantic divergence, it is also used extensively where a lemma has a low degree of translatability. The explicitness that can be achieved through the use of pictorial illustrations enhances the retrieval of information. This applies to both monolingual descriptive and translation dictionaries. Keywords: addressing, communicative equivalence, contextual information, convergence, divergence, encyclopedic information, equivalent relations, lexicography, meaning differentiation, ostensive addressing, pictorial illustrations, polysemy, pragmatic information, surrogate equivalent, transfer of information, transfer of meaning, translatability, translation dictionary